ANALISIS TREN DAN TRANSMISI HARGA BERAS DI INDONESIA SEBELUM DAN SELAMA PERIODE PANDEMI COVID-19 - Kusumaningsih, Asih (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
The stability of rice price in Indonesia is an important issue as is the price flow or price transmission between farmers and rice consumers in Indonesia, both prior  and during the COVID-19 pandemic. This research aims to determine trends in rice price at  farmer  and  consumer levels, and to examine the transmission of rice price between the rice market at  farmer  and consumer levels, both in the same situations: prior and during the COVID-19 Pandemic. The method used to analyze the price trends was  the Least Square method, while the process used to identify price transmission between markets at the farmer level and markets at the consumer level for the period before and during the COVID-19 Pandemic was the Engle-Granger Cointegration Test and ECM estimation. The research results show that the trend in rice prices at both  farmer  and  consumer levesl has a positive orincreasing trend before and during the COVID-19 pandemic. The price transmission that occurred between the rice market at the farmer level and the rice market at the consumer level or vice versa before the COVID-19 pandemic is  significant, or in other words do not experience a spurious phenomenon (meaningless regression), and price changes are  asymmetrical. The price transmission between the rice market at the farmer level and the rice market at the consumer level or vice versa during the COVID-19 pandemic is significant, experienced a spurious phenomenon (meaningless regression), and price changes are  asymmetrical. Keywords:   COVID-19, price, rice, transmission, trend